Determinants of loneliness during the COVID-19 pandemic in the United States: A one-year follow-up study. (December 2022) - Ray, Colter D.; Shebib, Samantha J.
An initial study on loneliness during the first month of the COVID-19 pandemic in the United States found that those who were living alone or who were single experienced greater loneliness than those who lived with others or were in a romantic relationship. This study presents follow-up analyses using data collected from the same sample ( N = 428) at a total of five points in time throughout the first year of the COVID-19 pandemic in the United States. Unlike most studies using a longitudinal design to track loneliness throughout the COVID-19 pandemic, the results of this study showed that loneliness scores generally decreased over this time period. However, additional analyses showed that when participants experienced a de-escalation in their romantic relationship status (e.g., transitioning from being in a dating relationship to being single or from being married to separated), loneliness scores increased. Because prior research shows a connection between living alone and loneliness, the researchers also tested whether decreases in the number of people one lives with predicted increases in loneliness. The data was inconsistent with this prediction. Overall, these findings join a minority of other longitudinal studies investigating loneliness during the COVID-19 pandemic that found either a decrease or no change in loneliness, while also illustrating that increases in loneliness during the COVID-19 pandemic occurred after people experienced a de-escalation in their romantic relationship status. These findings underscore the importance of life events during the COVID-19 pandemic that may increase loneliness—specifically transitioning out of romantic relationships. Thus, future research on predictors of loneliness should continue to use longitudinal designs to determine how changes in one's life predict changes in loneliness.